Minimally Invasive Direct Repair of Bilateral Lumbar Spine Pars Defects in Athletes - Gabriel A. Widi; Seth K. Williams; Allan D. Levi (Case Reports in Medicine)
Spondylolysis of the lumbar spine has traditionally been treated using a variety of techniques ranging from conservative care to fusion. Direct repair of the defect may be utilized in young adult patients without significant disc degeneration and lumbar instability. We used minimally invasive techniques to place pars interarticularis screws with the use of an intraoperative CT scanner in three young adults, including two athletes. This technique is a modification of the original procedure in 1970 by Buck, and it offers the advantage of minimal muscle dissection and optimal screw trajectory. There were no intra- or postoperative complications. The detailed operative procedure and the postoperative course along with a brief review of pars interarticularis defect treatment are discussed.